The earned income tax credit and maternal time use: More time working and less time with kids? - Jacob Bastian; Lance Lochner (W.E. Upjohn Institute for Employment Research, 2020)
Parents spend considerable sums investing in their children's development, with their own time among the most important forms of investment. Given well-documented effects of the Earned Income Tax Credit (EITC) on maternal labor supply, it is natural to ask how the EITC affects other time allocation decisions, especially time with children. We use the American Time Use Surveys to study the effects of EITC expansions since 2003 on time devoted to a broad array of activities, with considerable attention to the amount and nature of time spent with children. Our results confirm prior evidence that the EITC increases maternal work and reduces time devoted to home production and leisure. More novel, we show that the EITC also reduces time spent with children; however, almost none of the reduction comes from time devoted to "investment" activities. Effects are concentrated among socioeconomically disadvantaged mothers, especially those that are unmarried. Results are also most apparent for mothers of young children. Altogether, our results suggest that the increased work associated with EITC expansions over time has done little to reduce the time mothers devote to active learning and development activities with their children.
Keywords: D13; H24; H31; H53; I31; I38; J13; J22; 330; EITC; tax policy; time use; child investment; female labor supply